METAFISIKA MANUSIA MENURUT IMAM AL-GHAZALI - Asrizal Asrizal (UIN Sunan Kalijaga Yogyakarta, 2016)
The use of the term metaphysics has evolved since long to refer to things that are beyond the physical world. In everyday life, consciously or not human beings are always talking about things that smell metaphysics (trust). Humans understand the universe was created by God, but often people question how the form of God, in addition to the presence of a ghost or genie. It shows the relationship between humans and metaphysics. In this regard Imam al-Ghazali have different views in addressing the human metaphysics. Imam al-Ghazali considers humans have essentially fixed identity, as an-nafs (the soul). This paper would like to explain about the views of Imam al-Ghazali as a philosopherthe concept ofhuman metaphysics. In metaphysics Imam al-Ghazali, he based his views to the soul. The conclusion is that Imam al-Ghazali uses four terms in human metaphysics, as al-Nafs, al-Qulb, al-Ruhandal- 'Aqlused inphilosophical terms.